Research on hydraulic fracturing technology for the comprehensive management of gas gathering in the overhanging roof and upper corner of the upper end head - Pei, Zhang; Shuchao, Guo; Jiayao, Fu; Chenghong, Wu; Chunyu, Ji (Frontiers in Earth Science, 2025)
This study aimed to address the problems of large overhanging roof area and abnormal gas accumulation at the upper end of the 143 coal seam working face in the B42 mining area of Donggou Coal Mine, particularly the frequent exceedance of gas concentration limits at the upper corner of the working face. To solve these issues, the study first measured the gas concentration at the upper corner of the working face and analyzed the causes of frequent concentration exceedance, then applied hydraulic fracturing technology to conduct an overhanging roof treatment experiment—specifically, a drilling scheme was adopted to construct boreholes parallel to and perpendicular across the coal pillar along the roadway, and key parameters such as gas concentration, flow rate, and pressure in the overhanging roof area of the retreat mining face were determined before hydraulic fracturing, followed by comparing gas conditions before and after two rounds of hydraulic fracturing on the overhanging roof to analyze the gas control effect. The results showed that the strike length of the overhanging roof area at the upper end of the mining face decreased from 27–30 m to 5–8 m, the dip width reduced from 10–15 m to 2–5 m, the gas concentration at the upper corner of the working face ranged from 0.18% to 0.3%, the gas concentration in the goaf within 10–60 m was 0.6%–1.0%, and the gas concentration in the working face return airway stabilized at approximately 0.22; additionally, hydraulic fracturing and fractures generated by roof collapse promoted the massive upward migration of free gas in the upper corner to the area between the collapse zone and the fissure zone, ultimately controlling the gas concentration at the upper corner below 0.3%. These results confirm that hydraulic fracturing treatment effectively resolves the overhanging roof and abnormal gas problems of the 143 coal seam working face, fully meeting the requirements of coal mine safety regulations and providing a reliable reference for gas control under similar geological conditions.